Nilai-Nilai Pendidikan Akhlak Dalam Novel Diary Ungu Rumaysha Karya Nisaul Kamilah - Bambang Sugiyanto; Robingun Suyud El Syam; Nailul Khofifah (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the moral education values contained in the novel Diary Ungu Rumaysha by Nisaul Kamilah. It employs a qualitative approach using content analysis to examine how moral messages are conveyed through the characters, plot, and dialogues in the novel. The findings indicate five main aspects of moral education highlighted in the story: morality towards Allah, maintaining self-respect, devotion to parents and family, doing good to others, and restraining desires. These aspects are reflected in the journey of the main character, Rumaysha, who consistently upholds Islamic principles in her teenage life. The novel also conveys strong Islamic messages such as the values of worship (ubudiyah), humility (tawadhu’), perseverance (istiqamah), self-awareness (muraqabah), and self-control in facing the temptations of youth. The study concludes that Diary Ungu Rumaysha is a literary work rich in moral education values and is appropriate as a medium for character education for adolescents within the context of Islamic education.